Comparing Effects of Polypharmacy on Inflammatory Profiles in Older Adults and Mice: Implications for Translational Aging Research. Issue 7 (17th March 2022) - Wu, Harry; Mach, John; Gnjidic, Danijela; Naganathan, Vasi; Blyth, Fiona M; Waite, Louise M; Handelsman, David J; Le Couteur, David G; Hilmer, Sarah N
Abstract: Aging and multimorbidity are associated with inflammation. Polypharmacy is common in older people with multimorbidity. Given the potential for interactions between polypharmacy and inflammation, the relationship between inflammation and polypharmacy were studied in older adults with multimorbidity and in healthy aging mice. A cross-sectional analysis of data from the 5-year wave of the Concord Health and Ageing in Men Project, a population-based study of community-dwelling men aged ≥70 years. Serum concentrations of 27 cytokines were measured using a multiplex immunoassay. Associations between polypharmacy (≥5 medications) and cytokines were evaluated using multivariable linear regression adjusting for age, frailty, comorbidities, and individual drug classes. Interaction between polypharmacy and Drug Burden Index (DBI―drugs with anticholinergic and sedative effects) was analyzed. Effects of polypharmacy and DBI on serum levels of 23 cytokines were determined in aging male mice treated with chronic polypharmacy or control. Compared to the nonpolypharmacy group ( n = 495), CHAMP participants with polypharmacy ( n = 409) had significantly higher concentrations of IL-8, IL-6, CCL3, Eotaxin, IL-1ra, IL-1β, IP-10, and lower concentrations of anti-inflammatory cytokine IL-4. In fully-adjusted multivariable models, polypharmacy was positively associated with concentrations of IL-8 and CCL3. There were no significant differences in inflammatory profiles between control and polypharmacy-treated mice. The relationship was not influenced by DBI in men or in mice. Inflammatory markers associated with polypharmacy in older adults were not seen in healthy aged mice administered polypharmacy, and may be related to underlying diseases. The polypharmacy mouse model provides opportunities for mechanistic investigations in translational research.